Preparation and Characterization of Water-Insoluble Gardenia Blue Pigment - Yakun Gao (MDPI AG, 2021)
Based on molecular simulations, the synthetic route of water-insoluble gardenia blue pigment was prepared by the reaction of genipin and L-Phenylalanine methyl ester hydrochloride. A highly purified pigment was obtained after extraction by chloroform and purification by silica gel column chromatography, and the value of color is up to 288. A study on the structural characteristics of the pigment was implemented with a scanning electron microscope, ultraviolet-visible spectrophotometer, Fourier transform infrared spectrometer, X-ray photoelectron spectrometer, and quatropde-time of flight mass spectrometer. The results showed that the surface of the pigment was largely smooth and spherical; The λmax was 607 nm, and the main functional groups include O-C=O, C=O, C-N, C=C, OH, and benzene ring; We detrained six different molecular weight and chemical structures of pigments and speculated the particular structures and formation mechanisms of three kinds of pigment, whose molecular weights are 690.1156, 720.1226, and 708.1246 Da, respectively. The pigment was only able to be dissolved in ethanol, methanol, acetone, ethyl acetate, and other strong polar organic solvents, but was not able to be dissolved in water, ethyl ether, petroleum ether, and other weak polar organic solvents. In terms of light and thermal stabilities, water-insoluble gardenia blue pigment is significantly better than water-soluble gardenia blue pigment (p < 0.05). When it is under direct light for 7 days or incubated at 80–120 °C for 24 h, the pigment residual rates were 74.90, 95.26, 88.27, and 87.72%, respectively.